Good performance of turquoise killifish (Nothobranchius furzeri) on pelleted diet as a step towards husbandry standardization - Žák, Jakub (Sci Rep, 2020)
Dietary alteration is one of the most universally effective aging interventions, making its standardization a fundamental need for model organisms in aging. In this dietetic study we address the current lack of standardized formulated diet for turquoise killifish Nothobranchius furzeri – a promising model organism. We first demonstrated that N. furzeri can be fully weaned at the onset of puberty onto a commercially available pelleted diet as the sole nutrition when kept in social tanks. We then compared nine somatic and six reproductive parameters between fish fed a typical laboratory diet - frozen chironomid larvae (bloodworms) and fish weaned from bloodworms to BioMar pellets. Both dietary groups had comparable somatic and reproductive performance. There was no difference between diet groups in adult body size, specific growth rate, condition or extent of hepatocellular vacuolation. Fish fed a pelleted diet had higher juvenile body mass and more visceral fat. Pellet-fed males had lower liver mass and possessed a lipid type of hepatocellular vacuolation instead of the prevailing glycogen-like vacuolation in the bloodworm-fed group. No considerable effect was found on reproductive parameters. The negligible differences between dietary groups and good acceptance of pellets indicate their suitability as a useful starting point for the development of standardized diet for Nothobranchius furzeri.